Ontogenetic body‐mass scaling of nitrogen excretion relates to body surface area in diverse pelagic invertebrates. (10th October 2016) - Hirst, A. G.; Lilley, M. K. S.; Glazier, D. S.; Atkinson, D.
Abstract: Many physiological and ecological processes depend on body size and the supply of limiting nutrients. Hence, it is important to derive quantitative predictions based on a mechanistic understanding of the influence of body size on metabolic rate and on the ratios of consumed to excreted elements. Among diverse pelagic invertebrates that change shape during ontogeny, recent analysis has demonstrated a significant positive correlation between the body‐mass allometry of respiration rates (measured as the ontogenetic body mass‐scaling exponent bR ) and the allometry of body surface area ( bA, as predicted from body‐shape changes using a Euclidean model). As many pelagic invertebrates use a large portion of their external body surface for both resource uptake and waste excretion, we predicted that body‐mass scaling exponents for rates of excretion of soluble N ( bN ) should also then relate to the degree of body‐shape change during growth. We tested this hypothesis using literature data on bN for 39 species of pelagic invertebrates across five different phyla, and find strong support: bN is significantly positively correlated with predicted bA, whilst also co‐varying with bR . Intraspecific differences between bN and bR values reveal ontogenetic shifts in the ratio of O2 ‐consumed to N‐excreted. We suggest that a variety of factors, including adaptive developmental shifts in the relative anabolism and catabolism of proteins and lipids, may cause these shifts in consumption–excretion ratios. Diverse pelagic invertebrates that dominate vast open water ecosystems falsify the predictions of general metabolic scaling theories built upon resource‐transport networks, but support predictions of surface‐area dependent theory.